Money Versus Credit in the Determination of Output for Small Open Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
It is well known that in a small open economy where there is perfect substitutability between domestic and foreign assets and costless portfolio adjustment, the monetary authorities cannot control the money supply, but can influence the balance of payments through the use of domestic credit. It has been argued that domestic credit is therefore the relevant variable in output determination as well. However, this paper demonstrates, using a 'new classical' structural model, that under the conditions that render the money supply uncontrollable, neither money nor domestic credit affects output. If either has a significant effect in empirical tests, it implies that the assumption of perfect capital mobility is not satisfied.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet